Interdisciplinarity Of Paradigms Of Organizational Culture - Åukasik, Katarzyna; Bajdor, Paula; Budzik-NowodziÅ„ska, Iwetta; Brendzel-Skowera, Katarzyna (European Scientific Journal, ESJ, 2016)
The object of the paper is the cognitive analysis of the current of organizational culture in management. There have been considered the paradigms of social sciences and management, among others: Spencer functional paradigm, Drukheim functionalism, as well as the paradigms by G. Burrell and G. Morgan, significantly influencing the development of paradigms of organizational culture. The attention has been drawn to epistemological problems in defining the concept of organizational culture. The variety of the definitions of organizational culture results from the broad interest of researchers in this phenomenon, while simultaneously leading to lack in precision and order in its interpretation. The aim of the paper is an attempt to analyze the most important paradigms of organizational culture, originating from different scientific disciplines, creating the interpretation of the contemporarily understood concept and essence of organizational culture. The studies of literature concerning the analyzed research problem have been adopted as the research method. There has been proven the interdisciplinary nature of paradigms of organizational culture.